Amphibians and reptiles of the Sierra Gorda de Querétaro Biosphere Reserve, Mexico: species richness, conservation status and comparison with other natural protected areas in central Mexico - Raciel Cruz-Elizalde; Norma Hernández-Camacho; Rubén Pineda-López; Robert W. Jones (Revista Mexicana de Biodiversidad)
The Sierra Gorda de Querétaro Biosphere Reserve (SGQBR) is one of the largest natural protected areas in Mexico; however, little is known about the richness and diversity of amphibians and reptiles. We present an updated list of species of both groups, the conservation status of these species, as well as an analysis of their diversity with respect to other protected natural areas (NPAs) in central Mexico. The SGQBR contains 132 herpetofauna species (35 amphibians and 97 reptiles). The richest and most diverse families for amphibians were Hylidae (anurans) and Plethodontidae (caudates), and for reptiles Phrynosomatidae (lizards), Colubridae and Dipsadidae (snakes). The values of taxonomic diversity of the SGQBR were similar to those for the regional pool considering others NPAs. However, it did not achieve the highest values compared to the adjacent Los Mármoles National Park or Sierra Gorda de Guanajuato Biosphere Reserve. There was a high complementarity in the species composition between El Chico National Park and SGQBR for both herpetofauna groups. Although a formal list is presented, it is necessary to carry out a greater number of studies focused on analyzing diversity, considering functional attributes of the species and the richness by vegetation types.